Nutritional knowledge, nutritional status and food consumption of hypertensive and/or diabetic (Research, Society and Development, 2022)
Objective: To evaluate the level of nutritional knowledge and its association with the nutritional status and food consumption of hypertensive and/or diabetic patients at a Basic Health Unit in Maceió, Alagoas, Brazil. Methods: Cross-sectional study with a sample of individuals aged between 18 and 59 years. Demographic, socioeconomic, anthropometric (body mass index; waist circumference and; neck circumference), lifestyle, dietary and nutritional knowledge information were collected. Dietary data were collected using the food consumption frequency questionnaire. The nutritional knowledge score was stratified into “low knowledge”, “intermediate knowledge” and “sufficient knowledge”. A descriptive analysis of the variables was performed and the association between general nutritional knowledge, nutritional status, and food consumption was verified through analysis of variance, Tukey's multiple comparison test, and Pearson's correlation. Was considered significant p